Dust explosions in the process industries - Eckhoff, Rolf K. (Butterworth-Heinemann, 1997)
Provides an account of the existing practical and theoretical knowledge of the origin, development, prevention, and mitigation of dust explosions in the process industries. It offers an evaluation of prevalent activities, testing methods, design measures, and safe operating techniques in a critique of significant phases relating to the hazard and control of a dust explosion.